The Role of Local Community and The Barriers to Participation in A Mini Hydro Energy Project in Indonesia - Annisa Qurani; Ricardi Adnan (Universitas Djuanda, 2023)
The Indonesian government's policy to encourage the involvement of private companies to contribute to renewable energy (RE) projects affects the lives of the local community in the surrounding areas. However, the local community's role in the RE project implementation must be clarified. The study identifies a possible role for the local community to participate in the RE project. It examines the barriers to its participation under the lens of public-private-people partnership. The study was conducted in a mini hydro power plant project in Indonesia. Eight representatives from the village government, community members, and company management were interviewed. The data were analyzed and presented in a descriptive-qualitative manner. The study found that local community participation is needed to manage water as a natural resource for mini hydro power plants. Still, the need for explicit agreement on responsibility and benefit-sharing between the local community, village government, and private companies becomes the barrier to community participation. The findings emphasize the need for formal partnership to specify how local government, private businesses, and communities supposedly develop renewable energy as the basis to involve stakeholders at the local level.